Evaluation of the Sterile Insect Technique for the Control of the Melon Fly (Bactrocera cucurbitae) Under Laboratory and Semi-Field Conditions in Sri Lanka - Muditha Nawarathne; Lahiru Udayanga; Hasini Ekanayake; Bader Alhafi Alotaib; Ananda Pathirage; Nayana Siriwardena; Athula Jayarathne; Hassan Ammouneh; Mohamed M. M. Najim; Abou Traore; Tharaka Ranathunge (Insects)
The melon fly, Bactrocera cucurbitae, poses a severe threat to the country’s agricultural productivity, particularly in the cultivation of cucurbitaceous crops. This study was conducted to determine the ideal irradiation dose to be used to set up a Sterile Insect Technique (SIT)-based strategy to control B. cucurbitae outbreaks in Sri Lanka. A B. cucurbitae colony was established and maintained under standard laboratory conditions. Male pupae (100 pupae per treatment) were exposed to different radiation doses, namely 0 (control), 50, 60, 70, 80, 90, 100, and 110 Gy. The effect of irradiation on selected performance parameters such as survival, flight ability, fecundity, fertility, and adult longevity was evaluated under laboratory conditions. In addition, mating competitiveness was evaluated for irradiated male B. cucurbitae. Significant differences were observed in percentage pupal survival, flight ability, and fertility rates (p < 0.05) at a 95% level of confidence. Further, the 50% and 75% adult longevity periods of irradiated B. cucurbitae males significantly decreased with the increasing irradiation dosage (p < 0.05). B. cucurbitae exposed to 70 Gy radiation reported a mean pupal survival rate of 94.0 ± 1.25, flight ability of 93.3 ± 1.88, and fertility 0.2 ± 0.05%, along with a mean longevity of 38 ± 1.5 days until 50% reduction in the population. The competitiveness of B. cucurbitae exposed to 70 Gy with respect to wild males was 0.56 under laboratory conditions, which reduced up to 0.5 in semi-field settings. The 70 Gy dose could be recommended as the optimal radiation dose for the production of sterile B. cucurbitae males with an acceptable level of fitness and sterility to be used in SIT-based melon fly control programmes in Sri Lanka.